Understanding the Nano–Bio Interactions and the Corresponding Biological Responses - Tian, Xin; Chong, Yu; Ge, Cuicui (Frontiers in Chemistry, 2020)
Abstract: With the increasing development of nanotechnology, nanomaterials hold great promise for revolutionizing biomedicine. However, insufficient understanding of nanomaterial–biological microenvironment (nano−bio) interactions hinders the clinical translation of nanomedicine. Therefore, a systematic understanding of nano−bio interaction is needed for the intelligent design of safe and effective nanomaterials for biomedical applications. In this review, we summarize the latest experimental and theoretical developments in the fields of nano−bio interfaces and corresponding biological outcomes from the perspective of corona and redox reactions. We also show that nano−bio interaction can offer a variety of multifunctional platforms with a broad of applications in the promising biomedicine. The potential challenges and opportunities in the study of nano−bio interface are also provided.